Sanksi Hukum dan Tanggung Jawab Produsen Atas Penyalahgunaan Bahan Kimia pada Makanan - Sri Yunita; Olivia Febriana Gea; Siti Zahara; Happy Simaremare; Christy Sihombing; Elsa Situmorang (International Forum of Researchers and Lecturers, 2024)
Food is a substance consumed by living beings such as humans to obtain the necessary nutrients. When consuming it, food must be ensured to be good for the body's health. Food that contains harmful chemicals will cause damage to the organ systems. This article examines how the law and food business operators who use hazardous substances such as borax, formalin, and Rhodamin-B. A literature review of various regulations shows that business operators are legally obligated to be responsible for such actions. An analysis of the applicable legal framework indicates that business operators can be held civilly liable for the resulting damages. The results of this research have important implications for business operators, consumers, and policymakers in efforts to protect consumers from hazardous food products.